Respuesta :

Answer:

h =13

Step-by-step explanation:

[tex]11h - (2h-1) = 118\\\\\mathrm{Expand\:}11h-\left(2h-1\right):\quad 9h+1\\9h+1=118\\\\\mathrm{Subtract\:}1\mathrm{\:from\:both\:sides}\\9h+1-1=118-1\\\\Simplify\\9h=117\\\\\mathrm{Divide\:both\:sides\:by\:}9\\\frac{9h}{9}=\frac{117}{9}\\\\Simplify\\h =13[/tex]

Answer:

H=13

Step-by-step explanation:

First, remove the individual terms from parenthesis. Be careful to handle the signs of each individual term correctly:

to solve for  h

while keeping the equation balanced:

9 h 9 = 117 9

9 h 9 = 13